The natural interest rate in OLG modelling: A rehabilitation - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2018)
A simple OLG model is used to show that the natural interest rate is superior to the golden rule. This remains valid with public goods, provided these are financed in an appropriate way. In order to preserve the natural interest rate, the so-called helicopter money appears to be more appropriate than the normal credit money. Dynamic inefficiency cannot occur, if either land or neutral (helicopter) money is available as an alternative store of private wealth. Thus, the frequently proposed failure of OLG-models to satisfy the first fundamental theorem of welfare economics does not exist. The paper both generalizes and summarizes some key results from my recent book (van Suntum 2017).
Keywords: B22; D51; D90; E1; E4; 330